Association Between Parkinson's Disease and Inflammatory Bowel Disease: a Nationwide Taiwanese Retrospective Cohort Study. Issue 5 (26th February 2016) - Lin, Jung-Chun; Lin, Chin-Sheng; Hsu, Chin-Wang; Lin, Cheng-Li; Kao, Chia-Hung
Abstract: Objectives: Inflammatory bowel disease (IBD) is a chronic inflammatory disorder. Previous studies have suggested that chronic systemic inflammation increases the risk of Parkinson's disease (PD). This study examined the effects of IBD on the development of PD. Methods: In a nationwide population-based cohort of 23.22 million insured residents of Taiwan aged ≥ 20 years, we compared people diagnosed with IBD during 2000 to 2011 (n = 8373) with IBD-free individuals. Patients with PD were identified in the National Health Insurance Research Database. Using univariable and multivariable Cox proportion hazard regression models, we estimated the adjusted hazard ratio (aHR) for PD with a 95% confidence interval (CI) with adjustment for age, sex, and comorbidities. Results: In the cohort, IBD was associated with an increased incidence of PD (crude hazard ratio = 1.43, 95% CI = 1.15–1.79). The risk was highest among individuals with Crohn's disease (aHR = 1.40, 95% CI = 1.11–1.77). In the multivariable model, the risk of PD was increased for men (aHR = 1.28, 95% CI = 1.05–1.56) and higher for patients with hypertension (aHR = 1.72, 95% CI = 1.33–2.24), coronary artery disease (aHR = 1.31, 95% CI = 1.04–1.66), or depression (aHR = 2.51, 95% CI = 1.82–3.46). Conclusions: We suggest that IBD is associated with an increased risk of PD. Patients with IBD should be aware of the potential risk for PD development.